Aqueous solutions with information on solids: room-temperature phosphorescence of polysaccharide–benzophenone complexes. Issue 6 (26th January 2023) - Okuno, Masafumi; Yamana, Keita; Kawasaki, Riku; Konishi, Yuto; Ono, Toshikazu; Ishi-i, Tsutomu; Ikeda, Atsushi
Abstract : Water-soluble λ-carrageenan–benzophenone complexes retained their properties of crystallization-induced phosphorescence of benzophenones at room temperature in aqueous solutions. Abstract : Benzophenone and its derivatives emit crystallization-induced phosphorescence despite their simple structures. To easily modify their phosphorescence properties, we prepared phosphorescence-emitting aqueous solutions of polysaccharide–benzophenone and polysaccharide-4, 4′-difluorobenzophenone complexes, which exhibit excellent biocompatibility and biodegradability.